Paleobathymetry of a Pliocene Voutes coast (Heraklion, Crete). - Agiadi, K.; Koskeridou, E.; Triantaphyllou, M.; Karakitsios, V. (Bulletin of the Geological Society of Greece, 2013)
The fish otolith assemblages identified in the Zanclean sediments of Voutes section (Heraklion, Crete) are analyzed in order to estimate the depth of deposition. The assemblages indicate that Voutes area was in fact a coast inhabited by a neritic fish fauna with significant mesopelagic component, mostly Myctophids. The benthic and benthopelagic group exhibits great diversity. In the late Zanclean, the study area corresponds to a deep neritic environment, which gradually uplifts. At the end of the Zanclean, Voutes area becomes a very shallow coast, as shown by the increased contribution to the assemblage by members of the Gobiid family, as well as the notable presence of Bothidae. Thereafter, the area deepens again, as the shallow benthic-benthopelagic component significantly decreases. This is consistent with the appearance of Pteropods and reaches a peak during the deposition of diatomites at maximum depth. At the upper part of the section, the sea bottom depth decreases again to allow for the deposition of marls with various molluscs remains, where Gadids and Gobiids again reappear. Finally, the upper diatomitic horizon is characterized by a rather poor fish fauna. These observations allow reconstructing the evolution of Voutes coastal area during the latest Zanclean until the Piacenzian.